Interview with Pakistan's Ambassador to the United States - Qazi, Ashraf Jehangir (Tufts Archival Research Center, 2005)
Volume 28, Issue 2. Summer Pakistani Ambassador Ashraf Jehangir Qazi talks to The Forum about the India-Pakistan proposal for peace, A.Q. Khan's illicit nuclear activities, and the demands on the Pakistani leadership in the war on terrorism.